Effect of the COVID-19 pandemic on maternal and neonatal health services in three referral hospitals in Guinea: an interrupted time-series analysis - Tamba Mina Millimouno; Nafissatou Dioubaté; Harissatou Niane; Mamadou Cellou Diallo; Cécé Maomou; Telly Sy; Ibrahima Sory Diallo; Aline Semaan; Thérèse Delvaux; Lenka Beňová; Alexandre Delamou (BMC, 2023)
Abstract Introduction In sub-Saharan Africa, there is limited evidence on the COVID-19 health-related effect from front-line health provision settings. Therefore, this study aimed to analyse the effect of the COVID-19 pandemic on routine maternal and neonatal health services in three referral hospitals. Materials and methods We conducted an observational study using aggregate monthly maternal and neonatal health services routine data for two years (March 2019-February 2021) in three referral hospitals including two maternities: Hôpital National Ignace Deen (HNID) in Conakry and Hôpital Regional de Mamou (HRM) in Mamou and one neonatology ward: Institut de Nutrition et de Santé de l'Enfant (INSE) in Conakry. We compared indicators of health service utilisation, provision and health outcomes before and during the COVID-19 pandemic periods. An interrupted time-series analysis (ITSA) was performed to assess the relationship between changes in maternal and neonatal health indicators and COVID-19 through cross-correlation. Results During COVID-19, the mean monthly number (MMN) of deliveries decreased significantly in HNID (p = 0.039) and slightly increased in HRM. In the two maternities, the change in the MMN of deliveries were significantly associated with COVID-19. The ITSA confirmed the association between the increase in the MMN of deliveries and COVID-19 in HRM (bootstrapped F-value = 1.46, 95%CI [0.036-8.047], p < 0.01). We observed an increasing trend in obstetric complications in HNID, while the trend declined in HRM. The MMN of maternal deaths increased significantly (p = 0.011) in HNID, while it slightly increased in HRM. In INSE, the MMN of neonatal admissions significantly declined (p < 0.001) and this decline was associated with COVID-19. The MMN of neonatal deaths significantly decreased (p = 0.009) in INSE and this decrease was related to COVID-19. Conclusion The pandemic negatively affected the maternal and neonatal care provision, health service utilisation and health outcomes in two referral hospitals located in Conakry, the COVID-19 most-affected region.